DESIGN SPEED OF DEEP DRAFT VESSELS IN SHALLOW WATERWAY OF SANGKULIRANG RIVER - Pratama, Yugi
The purpose of this study is to determine the design speed of deep-draft vessels in shallow waterway of Sangkulirang River for providing safety navigation there. The method used in this research is analytical model by using equations which are developed by Gourlay (2007) and Barrass (1981). Gourlay (2007) equation is used to determine the maximum allowed squat using bathymetry data of Sangkulirang River and draft of deep-draft vessels data. And, Barrass (1981) equation is used to determine the design speed using the known maximum allowed squat which needs bathymetry and width data of Sangkulirang River also the beam and draft of vessels data. Finally, the design speed of deep-draft vessels in shallow waterway can be proposed for providing safety navigation in Sangkulirang River for large barge vessels is 9.7 knots, for large container vessels is 11.3 knots and for RoRo vessels is 17 knots. But those design speeds are calculated based only on the dimensions of waterway and vessels. Therefore it needs other factor to be included into calculations such as waterway traffic and interaction between vessels for better results.